PTU-172 Treatment Outcomes For Barrett's Oesophagus Related Neoplasia Have Improved Over Time With Changes In Endoscopic Practice: Five Year Experience From The First Five Hundred Patients In The United Kingdom Registry. (9th June 2014) - Haidry, RJ; Banks, M; Gupta, A; Butt, M; Fullarton, G; Smart, H; Morris, J; Willert, R; Narayanasamy, R; Rodriguez-Justo, M; Novelli, M; Lovat, L
Abstract : Introduction: Barrett's oesophagus (BE) is the recognised pre-cursor to oesophageal adenocarcinoma (OAC). Combined endotherapy with endoscopic mucosal resection (EMR) and Radiofrequency ablation (RFA) have emerged as alternatives to surgery for curative treatment of patients with BE related neoplasia over the past 5 years. Methods: We examine prospective data from United Kingdom (UK) registry of patients undergoing RFA/EMR for early neoplasia arising in BE since the launch of the registry in 2008. Primary outcomes for clearance of dysplasia (CR-D) and BE (CR-IM) at 12 months were assessed over two time periods, between 2008–2010 and from 2011–2013. In addition durability of successful treatment, progression to invasive OAC and changes in endoscopic practices were also analysed between the time periods. Before RFA, visible lesions were removed by EMR. Thereafter patients underwent RFA every 3 monthly and biopsies were taken at 12 months. New lesions appearing during RFA treatment were removed by rescue EMR. This treatment algorithm has remained unchanged over past 5 years. Results: We report on 510 patients who have completed treatment with 12 month histology over past 5 years. CR-D and CR-IM have improved significantly between the former and later time periods from 77% and 56% to 91% and 82% respectively (p < 0.0001). The use of EMR for visible lesions prior to initiating RFA has also increased from 48% to 60% (p = 0.013). Conversely need for rescue EMR has decreased significantly to 3% over the last two and half years compared to 13% during initial time period (p < 0.0001). Progression to invasive OAC is not significantly different (2.8% in 2011–2013 vs. 4% 2008–2010, p = 0.56). Conclusion: We report one of the largest series of patients undergoing RFA for BE neoplasia. Clinical outcomes have improved significantly over the past 5 years as endoscopists have more experience with improved lesion recognition, and more attention to resection of all visible lesions before RFA. As a result the requirement for rescue EMR during RFA has reduced. Although rate of progression to OAC is lower in the later part of the registry experience, this is not statistically significant and implies that despite advances in endoscopic imaging and technique the rate of progression remains in the region of 2–4% in these high risk patients. All collaborators of the UK RFA registry are acknowledged for their contributions to this work. Disclosure of Interest: None Declared.